Design for Impact: Wake Wadho, A Cultural Branding through Collaborative Design Model in Ngada Regency, East Nusa Tenggara - Ni Nyoman Sri Natih Sudhiastiningsih; Siti Chadijah (Journal of Visual Art and Design, 2022)
Wake Wadho is a trans-sectoral and interdisciplinary collaborative model that combines design thinking and rapid ethnography implemented in three traditional villages in Ngada, Middle Flores, East Nusa Tenggara, Indonesia. This collaborative model was born from a pilot program (IKKON) run by the Indonesia Creative Economy Agency (BEKRAF RI). This collaboration involved people from various backgrounds, such as design, art, and anthropology. The three traditional villages in Ngada Regency required more comprehensive action involving facilitation and empowering activities to develop a sustainable and creative ecosystem. The program activities were reviewed based on social, cultural, economic, and geopolitics aspects. This paper illustrates the usage of design as a tool to create sustainable livelihoods. It describes a collaborative design model that combines anthropological and design approaches to create an ‘Experience Journey’ (EJ) consisting of two categories: a service design recommended as a tourism scheme and a sustainable lifestyle product as a tangible product design. This output aimed to emphasize the part of empathy within the design process by considering the sociocultural aspect of the community’s everyday life. Furthermore, the products have authentic and inspiring stories behind them. The initial output was wrapped up in Wake Wadho as a cultural brand.